Stylistic Analysis in the Novel Pantai Kasih by Azmah Nordin (Malay Literature, 2023)
Stylistics is the knowledge of style related to the use of language. In creating a literary work, a writer implicitly uses stylistics as the main medium to shape his philosophy in conveying the messages, ideas, and worldview of his writing. To that extent, this study focuses on the stylistic analysis of Azmah Nordin's novel titled Pantai Kasih using the Stylistic Theory by Weber (1989). Therefore, there are three main objectives in this study, which are to identify comparative stylistic styles, to identify the stylistic style of destruction found in Pantai Kasih and to identify the stylistic style of linking through Pantai Kasih. The data analysis is qualitative as it involves the analysis of the text of Pantai Kasih. In relation to that, based on the research that was implemented, the results of the study found that there is indeed a stylistic style highlighted in Pantai Kasih including a comparative stylistic style that includes personification, metaphor, and simile. Meanwhile, the stylistic style of destruction only includes syncope and acronyms and the stylistic style of linking only includes allusion. Finally, this stylistics study is expected to be able to become a medium to dignify the field of stylistics as a soul in the world of Malay literature education. This is because the field of stylistics not only highlights the art of language, but also becomes a benchmark in the formation of morals and ethics in society.Full text: PDF